New species of Licaria, Ocotea and Persea (Lauraceae) from Mexico - Lorea-Hernández, Francisco G. (Instituto de Ecología, A.C., 2005)
Eight new species of Lauraceae from Mexico are described and illustrated, namely: Licaria phymatosa, L. quercina, L. siphonantha, Ocotea atacta, O. sarcodes, O. zoque, Persea chrysantha and P. obscura. The three Licaria species belong in the subgenus Licaria; L. phymatosa and L. siphonantha are close to L. excelsa and L. triandra, respectively, while L. quercina is related weakly to L. peckii. Both Ocotea atacta and O. zoque add to the species related to O. insularis, whereas O. sarcodes is rather isolated, distantly related to the species of the O. heydeana group. Features of Persea chrysantha connect it to P. hintonii, but the position of P. obscura is uncertain.